2023
DOI: 10.1002/jsfa.12452
|View full text |Cite
|
Sign up to set email alerts
|

Determining optimal nitrogen management to improve rice yield, quality and nitrogen use efficiency based on multi‐index decision analysis method

Abstract: BACKGROUND: Reasonable nitrogen (N) supply is critical for increasing rice yield while improving grain quality and nitrogen use efficiency (NUE). However, the trade-off relationship between yield, quality and NUE of rice under N management has not been well understood enough. In the present study, a 2-year field experiment was conducted to identify optimal N fertilizer management practices that resulted in high-yield, high-quality and high-NUE by using the technique for order preference by similarity to an ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Therefore, this study constructed comprehensive evaluation models of rice quality, and each treatment was ranked to obtain the optimal treatment. TOPSIS might be a suitable model for evaluating the comprehensive rice quality compared to GRD, ETM, and Fuzzy Borda; this result was consistent with Fei et al [21]. First, the TOPSIS of the average correlation coefficient was highest at 0.848 and the rank was consistent with Fuzzy Borda (Table 5).…”
Section: Multiple Evaluation Models Of Rice Qualitysupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, this study constructed comprehensive evaluation models of rice quality, and each treatment was ranked to obtain the optimal treatment. TOPSIS might be a suitable model for evaluating the comprehensive rice quality compared to GRD, ETM, and Fuzzy Borda; this result was consistent with Fei et al [21]. First, the TOPSIS of the average correlation coefficient was highest at 0.848 and the rank was consistent with Fuzzy Borda (Table 5).…”
Section: Multiple Evaluation Models Of Rice Qualitysupporting
confidence: 87%
“…Shi et al [20] comprehensively evaluated the rice quality (appearance, milling, cooking, and eating quality) of different nitrogen content management practices by the principal component analysis method and found that low nitrogen conditions were better for rice quality. Fei et al [21] used TOPSIS with the EW method to identify the optimal N fertilizer management practices leading to high yield, quality, and N use efficiency in rice. Zheng et al [22] used a TOPSIS assessment of the effects of humic acid on japonica rice production under different irrigation practices.…”
Section: Introductionmentioning
confidence: 99%